The Influence of Technology-based Learning Media on Understanding Indonesian Language Learning - Hasibuan, Zulhijjah; Sutikno; Rahmat Kartolo (PT Inovasi Pratama Internasional, 2026)
In the digital era, the use of technology in education is an urgent need, especially in improving the quality of Indonesian language learning. This study aims to analyze the effect of the use of technology-based learning media on the learning understanding of class VI students of SDN 089 Panyabungan. The research method used is an associative quantitative approach with a simple linear regression design. Data were collected through distributing questionnaires and comprehension tests to 25 students, then analyzed using SPSS software version 24. The results showed that the use of technology-based learning media was in the good category with an achievement of 78.4%. The media used included learning videos, interactive presentations, and educational applications. The level of student understanding of the Indonesian language subject matter was also in the good category, with a percentage of 76.8%. Inferential analysis showed a t-count value of 5.987 which was greater than the t-table of 2.064 at a significance level of 5% (df = 23), so the alternative hypothesis was accepted and the null hypothesis was rejected. This indicates a significant influence between the use of technology media and student learning comprehension. The regression equation obtained was Y = 12.74 + 0.625X, with a coefficient of determination (R²) value of 0.527. This means that 52.7% of students' learning comprehension variables are influenced by technology-based learning media, while the remaining 47.3% are influenced by other factors such as learning motivation, family background, and learning environment. This finding shows that learning media is not just a visual aid, but plays an important role in clarifying concepts, increasing student engagement, and making the learning process more enjoyable.